Analisis Kendala Implementasi Pembelajaran Aktif pada Siswa Sekolah Dasar dengan Partisipasi Belajar Beragam - Nanda Tresia Hutabarat; Sri Wahyuni Siregar; Sartika Sartika; Naila Zavira Sembiring; Nur Azizah Daulay; Khairunnisa Khairunnisa (Jurnal Keluarga Sehat Sejahtera, 2026)
The active learning model is a learning approach that places students at the center of learning activities through direct involvement in the learning process. However, the implementation of active learning models in elementary schools still faces various obstacles due to varying levels of student learning participation. This study aims to analyze the obstacles to implementing active learning models in elementary school students with varying levels of learning participation. The research method used is a literature study by reviewing various scientific journals and relevant academic sources regarding active learning in elementary schools. The analysis technique is carried out through the collection, reduction, and synthesis of data from various previous studies. The results of the study indicate that obstacles to implementing active learning models are influenced by differences in student characteristics, low learning motivation, limited learning media, suboptimal classroom management, and teacher readiness in implementing active learning strategies. In addition, the diversity of student participation levels means that not all students are able to actively participate equally in the learning process. Therefore, creative and adaptive learning strategies are needed so that active learning can run more effectively in elementary schools.